Muuttuva kotieläintalous ja vesistökuormituksen sääntely - Kauppila, Jussi; Ekholm, Petri; Niskanen, Olli; Valve, Helena; Iho, Antti (Itä-Suomen yliopisto, 2017)
Animal husbandry is a major source of nutrient loading. Both feed production and manure spreading cause nutrient emissions into ground and surface waters. In regions where intensive animal husbandry meets soils already rich in phosphorus, risk for eutrophication increases. This article analyses how livestock installations and manure spreading are regulated as potential sources of nutrient loading in Finland. The regulation is a complex mix of economic and command-and-control instruments. The agri-environmental subsidy scheme acts as the primary tool in regulating agricultural water pollution. In Finland, about 90% of farms have been committed to the agri-environmental scheme and its terms, but as shown in the paper, the share is decreasing and may well continue to do so as agricultural production continues to intensify. For the farms outside the agri-environmental scheme, general legal standards limit fertilisation, but in a less strict manner. Additional local restrictions can be established by municipal regulations. The environmental permit scheme covers vast majority of livestock installations. Stipulations issued in the permits do not only regulate the emissions from the livestock installation as a point source, but extend to regulate even the spreading of manure, which is often contracted out and spread on the fields by other farmers. The analysis indicates that the regulatory system suffers from unnecessary duplication, sometimes even incoherency. As a result, regulation seems to place a relatively high regulatory burden on farmers and authorities. Questions on optimal regulatory approach – and the role of legal standards and environmental permits in particular – are further stressed by ongoing structural development in livestock production: as farm size continues to grow and farms become ever more specialised, manure management will be decoupled from the livestock installation.
Envolving livestock production and the regulation of agricultural water pollution
Keywords: rakennemuutos; structural development; kotieläintalous; vesistönkuormitus; säännöstely; livestock production; eutrophication; regulations